Finland : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Finland. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights that Finland's economic growth has picked up considerably, broadening to exports and equipment investment, and the current account is back to surplus. The economic recovery is expected to remain strong in the near term, but potential growth is constrained by labor market rigidities and aging. The IMF projects growth of 2.8 percent in 2017 and 2.3 percent in 2018. Better-than-expected fiscal outcomes in 2016 are projected to continue in 2017, but the public finances face long-term challenges from a declining working age population and escalating age-related spending. Avoiding a procyclical fiscal stance would help rebuild buffers over the medium term.